Social media storytelling - Mueller, Marie Elisabeth; Rajaram, Devadas (Abingdon, Oxon, [English] Routledge, an imprint of the Taylor & Francis Group, 2023)
"Offering a radical new toolbox for digital storytellers, this key text contains everything today's media practitioners need to know about conceptualising, editing and producing stories for online platforms and audiences. This book teaches readers practical skills for increasing their reach online, strengthening their personal brand, and improving follower counts across the social web, including main platforms as Twitter, Snapchat, TikTok, Instagram and Facebook. Taking a DIY approach, the authors guide readers through which platforms are best suited to their users and how to customise stories for different channels. Topics covered include storytelling with smartphones (iOS and Android), storyboarding, framing, sequencing, shooting and editing high-quality content, and evaluating the success of content and campaigns. Contributions from five industry experts expand on privacy, community building, and collaboration. The book concludes by looking to the future of social media storytelling, with industry professionals offering predictions for trends to watch out for. Social Media Storytelling is an essential resource for students of mobile and multimedia journalism, digital media, and media marketing, as well as for professionals who want to learn how to create compelling content and tell impactful brand stories. The book also features accompanying online exercises"--Provided by publisher.
1. How can I make use of storytelling? -- 1.1. Facts tell, stories sell -- 1.2. What is social storytelling? -- 1.2.1. Listen to your followers -- 1.2.2. Find the right tone -- 1.2.3. Make your stories travel across relevant channels -- 1.2.4. Begin a long-term relationship with your community with social stories -- 1.3. Why is storytelling so impactful? -- 1.3.1. Stories wire visuals to our brains-- 1.3.2. Explain complex matters in simple stories -- 1.3.3. From hero to guide - guide users through your stories -- 1.4. How self storytelling works on your profiles -- get inspired by best practice examples -- 1.4.1. Personal profile stories -- 1.4.2. Community profile stories -- 1.4.3. Brand profile stories -- 1.4.4. Journalists profile stories -- 2. A radically new toolbox for social storytellers 2.1. Story anatomy in place of the 'hero's journey' 2.1.1. Farewell to the 'hero's journey' 2.1.2. Guides 2.1.3. Story anatomists -- 2.1.4. Nanoparticles -- 2.2. Find story beats -- 2.3. Show faces and voices -- 2.4. Develop micro-stories -- 2.5. Use multimedia layers -- 2.6. Make use of cross-platform methods -- 2.7. Collaborate with influencers -- 3. Professional storytelling with your smartphone in a mobile-first world -- 3.1. Content-focused communication -- 3.2. Integrated content strategy -- 3.3 Storytelling apps and templates for all -- 3.4 Ensure professional quality -- 3.5 Precise preparation and project management pay off -- 3.6 Visual, mobile, social -- 2.6.1 Smartphones, the all-rounders -- 3.6.2 Digital literacy 3.7 Design your narrative strategy -- 3.7.1 Engage with your users -- 3.7.2 Visualise your language -- 3.7.3 Experiment with user-oriented technology -- 3.8 What is quality content? -- 3.8.1 Short, relevant, profound, purposeful, rapid -- 3.8.2 Multimedia content -- 3.8.3 Interactive content -- 3.8.4 Immersive elements -- 3.8.5 Live is Life -- 3.9 The small multimedia ABC for social storytellers with their smartphones -- 3.9.1 External smartphone equipment -- 3.9.2 Shooting and framing -- 3.9.3 Photos -- 3.9.4 Videos -- 3.9.5 Shooting -- 3.9.6 Post-production -- 3.9.7 Audio and music -- 3.9.8 Texts -- 3.9.9 3D objects -- 3.9.10 360-degree spaces -- 3.10 Produce mobile stories in five steps -- 3.10.1 Storyboard -- 3.10.2 Framing -- 3.10.3 Recording and shooting -- 3.10.4 Writing -- 3.10.5 Sequencing and editing -- 4. Understand and implement mobile story genres -- 4.1. Smartphones change everything -- 4.2. Micro-storytelling -- 4.2.1. Hashtags -- 4.2.2. Memes -- 4.2.3. Feeds -- 4.2.4. Stories -- 4.2.5. Why stories and toks are replacing the newsfeed -- 4.3. In-built storytelling tools and platform specifics -- 4.3.1. Social+ companies -- 4.3.2. Digital shop windows vs. social storytelling -- 4.3.3. Twitter -- 4.3.4. TikTok -- 4.3.5. Snapchat -- 4.3.6. Instagram -- 4.3.7. Facebook -- 4.4. Explainer videos -- 4.5. Social audio -- 4.6. Live social TV -- 5. Find the best strategy -- 5.1. Integrated, convergent storytelling -- 5.2. How do I find good stories? -- 5.2.1. Search, find, verify -- 5.2.2. Story DNA -- 5.2.3. Platform-agnostic planning -- 5.3. How do I prepare best? -- 5.3.1. Facts, people, stories -- 5.3.2. Platform-specific planning and producing -- 5.4. An excellent concept is a must -- 5.4.1. Planning -- 5.4.2. Integrate and customise your micro-stories multiple times -- 5.4.3. Build a slow, long-form interactive story -- 5.4.4. Give data a face and tell data stories with data relevant for your followers and community -- 6. Evaluate your campaigns: Never without monitoring -- 6.1. Why do I use digital monitoring? -- 6.1.1. FMD ("Filmmakers Germany") campaigns as best practice examples -- 6.1.2. "Uganda Series 2018. Big five -- in the wild?" -- 6.1.3. Japan 2019/2020 -- Bucket list -- 6.2. What are relevant key performance indicators? -- 6.2.1. Evaluate the whole customer journey -- 6.2.2. Think sustainable instead click baits and likes -- 6.2.3. "All-in-one"-campaigns = content x reach x event, for instance, the "Usedom Sunspot Awards" -- 6.2.4. How do I evaluate in social media storytelling and content marketing? "The disruptive tragedy" -- 6.2.5. Generate leads and evaluate conversions -- 6.3. What makes your campaign a success? -- 6.3.1. No content without call-to-action -- 6.3.2. Plan and initiate user-generated content -- 6.3.3. Keep in touch with your community! -- 7. Everything remains different: What's next for storytellers? -- 7.1. Prepare for tech and storytelling trends of the near and medium future -- 7.2. What should you keep an eye on? Our expert tips -- 7.2.1 Deana Mrkaja: Tell immersive stories -- 7.2.2 Sascha Gottschalk: Work with user-generated content -- 7.2.3 Tim Hendrik Walter: Learning together in social stories -- 7.2.4 Maximilian Wolf: With edutainment and livestreams you are on the right track -- 7.2.5 Adil Sbai: Find creative solutions for copycats -- Authors and experts in this book.
Includes bibliographical references and index.
Keywords: Storytelling in mass media; Digital storytelling; Mass media -- Authorship; Storytelling -- Interactive multimedia